9 - Adekeye Adebajo, Building Peace in West Africa: Liberia, Sierra Leone and Guinea Bissau. Boulder: Lynne Rienner, 2002.192 pp. ISBN 1-588: par Samuel Ong'wen Okuro - Okuro , Samuel Ong' wen (Africa Development, 2004)
abstract